AN ANALYSIS OF QUALITY ASSURANCE IN ELEARNING: COURSE MANAGEMENT LEVEL - Achwarin, Naree (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
The purpose of the study was to examine the concepts and principles of quality assurance in eLearning for course management level. The author reviewed and analyzed the existing literature, researches, and case studies, particularly emphasized on quality assurance in eLearning process that relevant to the course management system, especially in course production process and delivery of eLearning. This study highlights an important view of the application of quality assurance concepts and principle through eLearning at course management level. Since the quality assurance system in eLearning concerns, involves with many people from different department and management level; administrators, teachers, IT technician, staffs, stakeholders, students and community, the quality assurance through eLearning at course management level required certain aspect of leadership and management for administrators and instructional leadership for instructors. The teaching-learning process for course development and management was categorized into 4 phases for course management level; planning and analysis for an online course, implement of design and course production, delivery the online course, and assessment and evaluation.